El método del elemento finito de la ingeniería mecánica - Muciño Quintero, Víctor Hugo (My University, 1982)
The development of an effective computer program for structural analysis requires a knowledge of three scientific discinlines structural mechanics, numerical analysis and computer application. The development of accurate and efficient structural elements requires a modern background in structural elements requires a modern background in structural mechanics. The efficiency of a program depends largely on the numerical techniques employed and on their effective computer implementation. With regard to programming techniques, an optimum allocation of high and low speed storage is necessary.
Keywords: dynamic; equilibrium; dimensional; thermal; vectors